Supporting web-based learning with CmapTools : an example from Portugal - Coutinho, Clara Pereira (2008)
In this study electronic concept mapping were used to support online learning activities in a post graduate teacher education program. For one semester, three teachers who couldn´t attend regular classes used CmapTools as a constructivist learning strategy to organise and communicate learning of the core concepts of the program. Teachers developed individual maps for the instructor to analyse and send feedback as part of the course formative assessment. Teachers could review, reflect and revise their concept map to be posted in the university platform. Students could accede to their peer maps in order to share ideas and leave comments. The use of concept mapping to support teachers distance learning was assessed thru final interviews. The goals were: a) to determine if building concept mapping influenced knowledge construction and understanding, b) to evaluate if electronic concept mapping were effective as a strategy to scaffold web-based distance learning environments.